KEEFEKTIFAN BAHAN PELINDUNG ALAMI DALAM MEMPERTAHANKAN INFEKTIVITAS Spodoptera exigua NUCLEOPOLYHEDROVIRUS (SeNPV) - Samsudin, Samsudin; Santoso, Teguh; Rauf, Aunu; Kusumah, Yayi Munara (Research Center for Biology-Indonesian Institute of Sciences, 2011)
Spodoptera exigua nucleopolyhedrovirus (SeNPV) is a viral pathogen of onion caterpillar S. exigua with high pathogenicity. One of the major constraints to the use of SeNPV for biocontrol of onion caterpillar is its sensitivity to ultraviolet (UV) degradation. The purposes of this research were to determine the effect of sunlight exposure on the virulence of SeNPV and to find out the effective natural UV protectant to maintain the SeNPV virulence. The results showed that the sunlight radiation affects the SeNPV infectivity. Addition of 1% of coconut shell charcoal, lampblack, husk charcoal, yam flour, molasses, yam filtrate, turmeric filtrate and green tea filtrate to the SeNPV suspension were found to be effective as UV protectant. Coconut shell charcoal, lampblack and husk charcoal are activated carbon that can absorb UV light. Yam filtrate is a natural ingredient that contains saponins and is able to protect SeNPV particles as reflectance. While molasses, turmeric filtrate and green tea filtrate containing flavanoid serve as a protective virus particles and UV absorber.